Outcome of Total Laryngectomy in Regional Hospitals of Bangladesh (Bangladesh Journal of Otorhinolaryngology, 2021)
Objectives: To analyze post operative complications, local recurrence, functional outcome of speech & swallowing and survival rate following total laryngectomy.Methods: This prospective observational study was done in four major tertiary care medical college hospitals of Bangladesh from July 2000 to December 2019. All operations were done by a single surgeon, one of the authors of this study based on the personal experience. 45 patients were selected who underwent total laryngectomy for biopsy proven advanced (T3 and T4) laryngeal cancer as primary case & recurrent cases following radiotherapy. Patients were followed up monthly for three months and then six monthly for two years and yearly for rest of their life.Results: Age of the patients ranged from 42 to 80 years with mean age 56.7 years. In postoperative period 03 (6.6%) patients developed wound infection, 03 (6.6%) stomal stenosis, 03 (6.6%) stomal recurrence, 02 (4.4%) seroma, 02 (4.4%) pharyngo-cutaneous fistula and 01 (2.2%) case developed pharyngeal stenosis. In post laryngectomy voice rehabilitation 33 (73.3%) cases used esophageal voice, 07 (15.5%) cases used electrolarynx and 05 (11.1%) cases used bloom singer valve. Out of oesophageal speech, 2 patients had poor speech, Regarding swallowing all patients had very good swallowing except one patient who got pharyngeal stenosis, needed dilation. 3 patients died in subsequent 2 years follow-up and overall survival was 93.3%.Conclusion: Outcome of total laryngectomy depends on site and size of tumour, nodal metastases, recurrent cases and co-existing co-morbidities. Total laryngectomy with or without radiotherapy offers significantly higher local control and survival benefit with advanced laryngeal cancer, compared to radiotherapy only.Bangladesh J Otorhinolaryngol 2021; 27(2): 139-144